2022
DOI: 10.3390/su15010127
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Sustainable Entrepreneurial Ecosystem in Qatar

Abstract: This study aims to contribute to the empirical literature on sustainable entrepreneurial ecosystems by understanding the opportunities and constraints to support its development using the case of Qatar. This study was designed using a triangulation method to combine different data collection techniques to increase the validity and reliability of the results. The data collection incorporated multiple data sources, starting with secondary sources and then collecting primary data through 37 interviews with key in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Government programs do not impact entrepreneurial activity. The reasons could be that governments do not design public policies and programs with a customer-centric view [52]. Research and development transfer lacks impact on entrepreneurial activity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Government programs do not impact entrepreneurial activity. The reasons could be that governments do not design public policies and programs with a customer-centric view [52]. Research and development transfer lacks impact on entrepreneurial activity.…”
Section: Discussionmentioning
confidence: 99%
“…Research and development transfer does not have a significant impact on entrepreneurial activity; some studies conducted in this region found that there exists low technology absorption, poor systems that enable digital payments, and the technology and knowledge transfer is limited by complex policies [43,46,47]. Government programs do not have a significant impact on entrepreneurial activity.…”
Section: Middle East Determinants Of Entrepreneurial Activitiesmentioning
confidence: 98%
See 3 more Smart Citations